The nature of the Eastern Extent in the outer halo of M31. Issue 2 (8th April 2021) - Preston, Janet; Collins, Michelle; Rich, R Michael; Ibata, Rodrigo; Martin, Nicolas F; Fardal, Mark
ABSTRACT: We present the first comprehensive spectroscopic study of the Andromeda galaxy's Eastern Extent. This ∼4° long filamentary structure, located 70–90 kpc from the centre of M31, lies perpendicular to Andromeda's minor axis and the Giant Stellar Stream and overlaps Stream C. In this work, we explore the properties of the Eastern Extent to look for possible connections between it, the Giant Stellar Stream and Stream C. We present the kinematics and photometry for ∼50 red giant branch stars in seven fields along the Eastern Extent. We measure the systemic velocities for these fields and find them to be −368 km s −1 ≲ $v$ ≲ −331 km s −1, with a slight velocity gradient of −0.51 ± 0.21 km s −1 kpc −1 towards the Giant Stellar Stream. We derive the photometric metallicities for stars in the Eastern Extent, finding them to be metal-poor with values of −1.0 ≲ [Fe/H]phot ≲ −0.7 with an 〈[Fe/H]phot 〉 ∼ −0.9. We find consistent properties for the Eastern Extent, Stream B and one of the substructures in Stream C, Stream Cr, plausibly linking these features. Stream Cp and its associated globular cluster, EC4, have distinctly different properties indicative of a separate structure. When we compare the properties of the Eastern Extent to those of the Giant Stellar Stream, we find them to be consistent, albeit slightly more metal-poor, such that the Eastern Extent could plausibly comprise stars stripped from the progenitor of the Giant Stellar Stream.